Pengaruh Visibilitas Media Dan Digital Bank Terhadap Pengungkapan Laporan Keberlanjutan Dengan Tata Kelola Sebagai Variabel Moderasi - Subagyo, Bambang; Murwaningsari, Etty (Technomedia Journal, 2023)
The purpose of this study to examine the impact of media visibility and digital banks on sustainability reporting disclosure, as well as the impact of corporate governance in moderating the media visibility and digital banks on sustainability reporting disclosure. The population used in this study are companies sector banking which listed in the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The sampling technique used purposive sampling technique with the analysis model is a multiple regression model. The results of the study indicate that the presence of media visibility and digital banks has a negative effect on sustainability reporting disclosures. The results show that corporate governance through the composition of independent commissioners has a positive effect when moderating the media visibility and digital banks on sustainability reporting disclosure.